PP14 The role of sensory impairments, problems of balance in accidental injury at work: a case-control study. (2nd September 2014) - D'Angelo, S; Harris, EC; Linaker, C; Coggon, DNM; Palmer, KT
Abstract : Background: Sensory impairments and disorders of balance are becoming increasingly common in ageing workforces. Most studies of sensory impairments and risk of injury in the workplace have relied on self-report, both of injury and of health impairment, and have been retrospective in design, with the potential for overestimation of risks. We aimed to assess the role of sensory impairments and disorders of balance in occupational injury in a database that prospectively records medical events. Methods: Using the Clinical Practice Research Datalink, which registers all medical consultations, referrals and diagnoses in primary care for 6% of the British population, we identified 1348 working-age patients who had consulted medical services over a 20-year period for workplace injury (cases) and 6652 matched controls. Risks were assessed by conditional logistic regression, for earlier recorded diagnoses of visual impairment, common eye diseases, hearing loss, perforated ear drum, non-acute otitis media, and disorders of balance. Results: In all, 793 subjects had an ear problem before the date of injury consultation (including 336 with impaired hearing and 483 with non-acute otitis media), 173 had an eye problem and 266 a disorder of balance. Odds ratios (ORs) were moderately elevated for hearing and visual problems overall and higher still in relation to blindness or partial sight (OR 1.90) and non-acute otitis media (OR 2.03). The OR for consulting with a disorder of balance within the 12 months immediately preceding injury consultation was 1.81 (95% CI 1.03–3.17). No associations were found with perforation of the ear drum or specific eye diseases. Conclusion: Impairment of hearing, problems of vision, and disorders of balance all appear to carry moderately increased risks of occupational injury.